Somatic and cognitive-affective depressive symptoms among patients with heart disease: differences by sex and age - Carina Aparecida Marosti Dessotte; Fernanda Souza Silva; Rejane Kiyomi Furuya; Marcia Aparecida Ciol; Jeanne Marie Hoffman; Rosana Aparecida Spadoti Dantas (Universidade de São Paulo, 2015)
OBJECTIVE: this study investigated the association of somatic and cognitive-affective symptoms with sex and age, among patients hospitalized with heart disease. METHOD: this study was a secondary analysis of two previous observational studies totaling 531 patients with heart disease, hospitalized from 2005 to 2011 in two public hospitals in Ribeirão Preto, state of São Paulo, Brazil. Somatic and cognitive-affective symptoms were assessed using the subscales of the Beck Depression Inventory - I (BDI-I). RESULTS: of 531 participants, 62.7% were male, with a mean age 57.3 years (SD= 13.0) for males and 56.2 years (SD= 12.1) for females. Analyses of variance showed an effect of sex (p<0.001 for somatic and p=0.005 for cognitive-affective symptoms), but no effect of age. Women presented with higher mean values than men in both BDI-I subscales: 7.1 (4.5) vs. 5.4 (4.3) for somatic, and 8.3 (7.9) vs. 6.7 (7.2) for cognitive-affective symptoms. There were no differences by age for somatic (p=0.84) or cognitive-affective symptoms (p=0.84). CONCLUSION: women hospitalized with heart disease had more somatic and cognitive-affective symptoms than men. We found no association of somatic and cognitive-affective symptoms with age. Future research for these patients could reveal whether these differences according to sex continue throughout the rehabilitation process.